Socialization of the Training Program During the Covid-19 PPKM Period and Field Lighting at the Gloria Muda Tambakrejo Volleyball Club, Bulurejo Village - Edi Irwanto; Danang Ari Santoso; Bayu Septa M.T; Arya T Candra; Achmad Zayul Mustain (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2022)
The purpose of this activity is to socialize the training program during PPKM Covid-19 and field lighting at the Gloria Muda Tambakrejo volleyball club, Purwoharjo, Banyuwangi Regency. The method used is discussion, practice, and direct handling (demonstration, practice and handling) of players and the Gloria Muda volleyball court lighting system. The result of this activity is an increase in the physical condition and skills of the players, as well as field lighting that is in accordance with training standards.